Pengaruh Model Project Based Learning Berbantuan Media Color Paper Terhadap Kemampuan Menulis Permulaan Siswa - Jannah, Elya Maliyatul; Yanto, Ari (Jurnal Ilmiah Pendidik Indonesia, 2023)
Skills are the result of the learning process in the psychomotor domain, which is formed to resemble learning outcomes in the cognitive domain. Skill is the ability to do or do something well. The purpose of this opinion, ability is the skills and potential possessed by a person to master a skill he has from birth. This ability is something that will happen like the exercise that is used to do something. Beginning writing skills are needed to practice writing skills at the beginning of low grade children. With the aim to be trained in writing. Project Based Learning (PjBL) is a learning model that uses a project or activity as a medium. Students carry out exploration, assessment, interpretation, synthesis, and information to produce various forms of learning outcomes. The method of writing this scientific work is to use literate studies (library research). The results of this study are expected to provide an overview for developing further research regarding the project based learning model and integrated into other learning.